2023
DOI: 10.1177/27536386231163721
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of non-conveyance following an Australian ambulance service paramedic response: A constructivist grounded theory exploration

Abstract: Understanding patient experience is associated with quality, safe, and effective healthcare. However, there is a scarcity of knowledge explaining how patients experience non-conveyance, a setting where individuals receive unscheduled ambulance service response and paramedic-led care that results in a decision to not attend a hospital emergency department (ED). This research project aimed to investigate patients’ experiences of non-conveyance within an Australian ambulance service setting. Constructivist Ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Nonconveyance has been found to also potentially be a positive experience for a patient through the restoration of self-efficacy following a loss of independence to manage their individual circumstances. 46 Empowering standard care paramedics to increase the nonconveyance rate will have benefits on addressing worsening hospital ramping within Australia alongside increased response times for the communities that they serve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonconveyance has been found to also potentially be a positive experience for a patient through the restoration of self-efficacy following a loss of independence to manage their individual circumstances. 46 Empowering standard care paramedics to increase the nonconveyance rate will have benefits on addressing worsening hospital ramping within Australia alongside increased response times for the communities that they serve.…”
Section: Discussionmentioning
confidence: 99%
“…Specialist paramedics have already demonstrated a reduction in overall patient contact time due to high nonconveyance rates, 22 and as such there is significant potential to increase the scope of practice of standard care paramedics to offer greater levels of care. Nonconveyance has been found to also potentially be a positive experience for a patient through the restoration of self‐efficacy following a loss of independence to manage their individual circumstances 46 . Empowering standard care paramedics to increase the nonconveyance rate will have benefits on addressing worsening hospital ramping within Australia alongside increased response times for the communities that they serve.…”
Section: Discussionmentioning
confidence: 99%
“…It is also shown that non-conveyed patients have a risk of being exposed to adverse events [ 3 , 10 , 27 , 28 ] and the non-conveyed patients often seek medical care within 72 h after assessment made by ambulance clinicians [ 29 ]. The patients’ experiences of being non-conveyed are described as ‘complex and versatile’ [ 30 ], satisfying by being empowered in the decision-making, or as negative experiences when concerns were not confirmed by the ambulance clinician [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%